Should We Consider Alternatives to Universal Well-Child Behavioral-Developmental Screening? - Urkin, Jacob; Bar-David, Yair; Porter, Basil (Frontiers in Pediatrics, 2015)
The prevalence of developmental disabilities in the young age is of the order of 15%. When behavioral and social-emotional disorders, physical impairments and sensory disorders are included, the need for special intervention increases to one out of four children. As the sensitivity and specificity of the best screening tests are in the range of 70-80%, their predictive value is controversial. The cost of conducting definitive tests and repeat screening for those who fail the screening tests is high. Children with severe disorders can be identified clinically without a screening test. The poor predictability, difficulty in implementation and the high costs of developmental testing suggest that children, particularly those in high risk communities, might be better served by implementing intervention programs for all, instead of trying to identify the outliers through screening.